Translation of PhET simulations in Ibibio language: A seamless and culturally responsive learning of mathematics in Akwa Ibom State - Ekemini T. Akpan; Ememobong O. Udoh (Universitas Papua, 2026)
This paper discussed the translation processes of PhET interactive simulation into Ibibio langauge in the concept of special angles. The study uses the translated PhET applet to design a seamless and culturally responsive approach of learning the concepts of special angles, and to assess the academic achievement of students in special angles. The study was quasi-experimental, with three treatment groups, purposively sampled. The findings show that students taught the concept of special angles using PhET interactive simulations with culturally responsive approach obtained significantly higher academic achievement scores when compared to their counterpart taught the same concept using Interactive Lecturing Approach. Although the study yielded a high statistical power, there was no practical significant difference on students’ academic achievements when taught special angles using PhET interactive simulations with culturally responsive approach, and when taught the same concept using PhET interactive simulation without culturally responsive approach. Gender exerted a non-significant influence on students’ academic achievements among the groups. Hence, using PhET interactive simulations with mother tongue features, enhanced academic achievement of students, and contextual instructional delivery in Mathematics. Also, the study underpins situated understanding of Mathematical concepts, leading to optimal learning experiences. In the same vein, it fosters the enculturation of mathematical concepts, glocalization of ethnopedagogical techniques, and reverts the extinction of mother tongue in the Nigerian culture. It was recommended that virtual and culturally responsive strategies should be adopted by instructors to diversify instructional delivery in mathematics education.